Reducing the Welfare Dependence of Single-Mother Families: Health-Related Employment Barriers and Policy Responses - Jean Kimmel (W.E. Upjohn Institute for Employment Research, 1996)
The problem of rising health care costs and the related increased dependency on health insurance coverage has moved to the forefront of the U.S. policy agenda in recent years and was a fundamental component of President Clinton's 1992 campaign platform. However, the President's 1994 health care reform proposal was unsuccessful, and current GOP proposals to cut the rate of growth of Medicare and Medicaid spending while the eligible population and costs both continue to grow fail to address the problem of coverage. In fact, one likely side effect of the cost-shifting to private insurance carriers will be to increase the ranks of the uninsured. This paper addresses one aspect of the coverage problem: specifically, how do the competing interests of public and private coverage for single mothers affect these mothers' willingness to participate in the labor market? And, how might restrictions concerning welfare eligibility currently undergoing legislative debate enter into the equation?
Additional information: A revised draft with the title "Reducing the Welfare Dependence of Unmarried Mothers: Health-Related Employment Barriers and Policy Responses" appears in Eastern Economic Journal Vol. 23, No.2 (Spring 1997).
Keywords: J0; J2; J4; 330; single; mothers; Kimmel; Medicare; Medicaid; work